2022
DOI: 10.3389/fmicb.2022.998160
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a novel acidophilic β-xylanase from Trichoderma asperellum ND-1 and its synergistic hydrolysis of beechwood xylan

Abstract: Acidophilic β-xylanases have attracted considerable attention due to their excellent activity under extreme acidic environments and potential industrial utilizations. In this study, a novel β-xylanase gene (Xyl11) of glycoside hydrolase family 11, was cloned from Trichoderma asperellum ND-1 and efficiently expressed in Pichia pastoris (a 2.0-fold increase). Xyl11 displayed a maximum activity of 121.99 U/ml at pH 3.0 and 50 • C, and exhibited strict substrate specificity toward beechwood xylan (K m = 9.06 mg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Figure 6 illustrates the preservation of various residues, including aromatic residues, in the active site of GH10 xylanases, particularly the three tryptophan residues (Trp87, Trp271, Trp279) that actively contribute to substrate binding ( Boonchuay et al, 2016 ). Moreover, two histidine residues (His83 and His209) play vital role in forming hydrogen bond networks, while a conserved lysine residue (Lys50) has an impact on the K m value ( Li et al, 2017 ; Zheng et al, 2022 ). BvelXyn11 shared 100% identity with XynA (GenBank No: WP_007407578.1) from B. subtilis ( Rhee et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 illustrates the preservation of various residues, including aromatic residues, in the active site of GH10 xylanases, particularly the three tryptophan residues (Trp87, Trp271, Trp279) that actively contribute to substrate binding ( Boonchuay et al, 2016 ). Moreover, two histidine residues (His83 and His209) play vital role in forming hydrogen bond networks, while a conserved lysine residue (Lys50) has an impact on the K m value ( Li et al, 2017 ; Zheng et al, 2022 ). BvelXyn11 shared 100% identity with XynA (GenBank No: WP_007407578.1) from B. subtilis ( Rhee et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of rSrocXyn10-Ec and rBvelXyn11-Ec on SDS-PAGE (55 kDa for rSrocXyn10-Ec and 27 kDa for rBvelXyn11-Ec) are consistent with the general characteristics that xylanases belonging to GH10 family show a relative high molecular weight (≥ 30 kDa), and xylanases belonging to the GH11 family share a relative low molecular weight (< 30 kDa) ( Gavaseraei et al, 2021 ; Mendonca et al, 2023 ). For example, xylanase (from B. cereus L −1 ) ( Zhang et al, 2023 ), Xylanase II (from Aspergillus sydowii ) ( Brandt et al, 2020 ) and Xyl11 (from Trichoderma asperellum ND-1) ( Zheng et al, 2022 ) belonging to GH11 showed molecular weights of 23 kDa, 23.52 kDa and 22.47 kDa, respectively; and xylanase from Penicillium menonorum SP10 ( Luong et al, 2023 ), AS1 (from B. altitudinis ) ( Chauhan et al, 2023 ) and SipoEnXyn10A (from S. ipomoeae ) ( Xian et al, 2019 ) belonging to GH10 showed molecular weights of 54 kDa, 43 kDa and 44 kDa, respectively. Due to the random hydrolysis of the internal β-1,4-glycosidic bond of xylan, the hydrolysis product of endo-xylanases consisted of xylose and XOSs, demonstrating that rSrocXyn10-Ec and rBvelXyn11-Ec both endo-xylanases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us examine some of those dealing with the production of thermostable enzymes. These are mainly enzymes from various fungal species, but there are also bacterial ones, either in a native form or in a mutant form with elevated thermal stability (see Table 3) [41,161,[241][242][243][244][245][246][247][248][249][250][251][252][253]. Based on the data presented in Table 3, it can be concluded that to date, K. phaffii has been successfully used as a platform for the expression of heterologous genes to produce recombinant xylanases with high activity, stability at acidic pH, and high thermostability, e.g., xylanase enzyme preparations from the fungus Bispora sp.…”
Section: Xylanasementioning
confidence: 99%
“…Let us examine some of those dealing with the production of thermostable enzymes. These are mainly enzymes from various fungal species, but there are also bacterial ones, either in a native form or in a mutant form with elevated thermal stability (see Table 3 ) [ 41 , 161 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 ].…”
Section: K Phaffii As a Producer Of Enzymes For Increasing N...mentioning
confidence: 99%